Título Padrão - Nomura, Hitoshi; da Cruz, João Francisco (Arquivos de Ciências do Mar, 2018)
During 1965- 1966 (October-January) fishing season of the Atlantic blackfin tuna, Thunnus atlanticus (Lesson), 611 specimens caught with trolling line thrown from sailing boats near the waters bordering Rio Grande do Norte and Paraíba States (Brazil), were measured and weighted at the fishing center of Baía Formosa (Rio Grande do Norte).